Variação de desempenho zootécnico e sobrevivência de juvenis de Pomacea bridgesii mantidos em diferentes dietas, densidades e salinidades - Rodrigues, Lucas Cipriano (2024)
The cultivation of Pomacea bridgesii has proven to be a good alternative to meet the demand of ornamental aquariums and a possible non-conventional gastronomic use. The present study aimed to estimate the development of juvenile P. bridgesii with natural and artificial diets, to prove the negative effect of salinity on development, to investigate the consequences of different densities and to verify the result of feeding on the centesimal composition of the muscle of adult animals. In the first part of the experiment (67 days), the juveniles were randomly selected and transferred to the ponds. Seven different diets were provided, 3 artificial (RCO, RCA and RPE) and 4 natural (AV, CE, EL and AG). Each diet was maintained at stocking densities of (6, 10 and 14) animals/L. The animals fed with the artificial diets were acclimated to different salinities (0, 2 and 4) parts per thousand (ppt). The second part (75 days) was the cultivation of adult animals fed the same diets, at a density of 0.4 animal/L, kept in fresh water. The third part (8 days) was the analysis of the centesimal composition of the muscles of the adults. The water quality parameters analyzed (temperature, dissolved oxygen and pH) remained within the ideal range for all treatments, with no statistical divergence (p>0.05), with an average of 24°C, 4.7 mg/L and 7.0, respectively. The negative effect of salinity on performance was confirmed, mainly on survival, ranging from 88% in S0 to 24% in S4 (p≤0.05). The negative effect of densification (p≤0.05) was observed in all parameters analyzed with the exception of survival between 3V and 7V. There was a significant divergence (p≤0.05) in the performance results in relation to the diet, with the artificial ones being better than the natural ones, with emphasis on RPE that presented superior results for most parameters (weight gain: 0.71 ± 0.15, average final growth: 2.11 ± 0.42, specific growth rate: 1.73 ± 0.12, biomass change: 10.67 ± 0.23, feed efficiency: 2.03 ± 0.08, and apparent feed conversion: 3.75 ± 0.27). There was no statistical difference (p>0.05) in the observations of the bromatological composition of the P. bridgesii muscle (crude protein: 13%, lipid: 1%, moisture: 80%, ash: 3% and carbohydrate: 3%).